2016
DOI: 10.1002/pssa.201600187
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of indole and 3‐methylindole using boron‐doped diamond electrodes

Abstract: The simultaneous electrodetection of indole and 3methylindole was investigated in this paper. The detection was performed using a boron-doped diamond (BDD) electrode to take advantage of its remarkable electrochemical properties (Fujishima et al., Diamond Electrochemistry (Elsevier, 2005) [1]. In order to improve the selectivity between indole and 3-methylindole, square-wave voltammetry (SWV) was used. We showed that BDD electrodes fouled either from oxidation of indole or 3-methylindole could be efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The (100%) intensity peak at 26.69° relates to plane 320, while at 40.50° relates to plane 521. 41 Peaks at 29.44° and 26.5° (002 planes) indicate the carbonaceous support. 42 Additional peaks that were not assigned were attributed to the deposition of some plant-related inorganic or bioorganic phases that crystallizes over the surface of particles.…”
Section: Resultsmentioning
confidence: 99%
“…The (100%) intensity peak at 26.69° relates to plane 320, while at 40.50° relates to plane 521. 41 Peaks at 29.44° and 26.5° (002 planes) indicate the carbonaceous support. 42 Additional peaks that were not assigned were attributed to the deposition of some plant-related inorganic or bioorganic phases that crystallizes over the surface of particles.…”
Section: Resultsmentioning
confidence: 99%
“…This electrode fouling was likely related to the electrochemical polymerization of indole, as has been reported previously. 17 BDD holds an advantage here due to its resistance to fouling and its ability to be electrochemically cleaned in situ. 19 The material of the electrode can have a large effect on the mechanisms and efficiency of ECL reactions and so the effect of a new electrode must be investigated.…”
Section: ■ Results Andmentioning
confidence: 99%
“…Previously, the use of a similar, shorter and even more intense train of cathodic pulses (−100 mA cm −2 , 3 pulses of 100 ms duration with a duty cycle of 90 %; q pt =−27 mC cm −2 ) was reported as being sufficient to keep a BBD microelectrode active for the quantification of uric acid in urine diluted in a pH 7.2 phosphate buffer saline solution . More recently, Belghiti et al . reported that the reactivation of a BDDE directly in a 0.3 mol L −1 KCl solution containing 3‐methylindole was not successful; hence, to attain the simultaneous determination of 3‐methylindole and indole, a train of 40 alternating pulses in 3 mol L −1 LiClO 4 was used to reactivate the BDDE: ±50 mA cm −2 (equal duration of 500 ms; thus, a total activation time of 40 s and q pt =±1 C cm −2 ).…”
Section: Different Approaches To Electrochemical Pretreatmentsmentioning
confidence: 99%